The lived experience of transgender people of talking therapies. Issue 2 (2nd April 2016) - Applegarth, Gemma; Nuttall, John
ABSTRACT: New ways of thinking about gender identity have led to a transformation in transgender care from the psychological professions. Historically, the change can be seen as a move from treating transgender people as insane, to having a medical condition, and finally as individuals with a legitimate and acceptable gender identity. The psychological therapy professions have responded with guidelines and standards of care urging therapists to adopt an affirmative approach to the individual's unique experience of gender. Despite this, few studies have looked at the subjective experience transgender people have of psychotherapy. In response to this a qualitative research project was undertaken to explore the lived experience that six transgender people had of talking therapies. Using interpretative phenomenological analysis four master themes emerged from the interview data. These are "a fearful time, " "becoming comfortable with their personal gender, " "the importance of the relationship with the practitioner, " and a sense of "moving beyond therapy." This article gives some background to the project, its execution, and its findings. The research highlights that for transgender people psychotherapy remains a fearful encounter, often associated with medical intervention. However, the quality of the therapeutic relationship can bring acceptance of self and hope for a future beyond therapy. The research brings valuable insight for therapists working with transgender clients and adds to the theory and practice of psychotherapy with signposts for training and future research.